A Statutory Vetting Scheme for the Children's Workforce in New Zealand: Rights, Responsibilities And Parameters - Lynch, Nessa (Victoria University of Wellington Law Review, 2013)
New Zealand is unusual amongst comparable jurisdictions in lacking a statutory scheme to vet and possibly disqualify 'risky' individuals from working or volunteering with children. The current vetting process in New Zealand is ad hoc and not transparent. The Government has signalled its intention to place vetting on a statutory footing through the Vulnerable Children Bill. This article considers the appropriate parameters of a vetting scheme, considering the experiences of jurisdictions with established schemes.